Job burnout degree and its relationship to the effectiveness of performance in the special education of female teachers in private day care centers in Riyadh city - Al- Omar, Hussa Fahad Mohammed; Al- Enezi, Naif Amash Swailm (Journal of Educational and Psychological Sciences, 2021)
The study aimed to know the job burnout degree and its relationship to the effectiveness of performance in the special education of female teachers in private day care centers in Riyadh city, the study adopted the descriptive approach in a correlative manner and used the questionnaire for data collection. The study community is consist of all the female special education teachers in private day care centers in Riyadh city, and the sample of the study reached (256) female teachers selected randomly from the study community, and the results of the study resulted in a number of results, most significant the following: The study sample agreed with the high of job burnout degree in the private day care centers in Riyadh city, where it came a high degree in emotional exhaustion, then a medium degree in reduced personal accomplishment, And a medium degree in depersonalization, And The study sample agreed with the level of effectiveness of performance in the private day care centers in Riyadh city with a high degree, And The existence of a statistically significant reflexive relation relationship at the level of indication (0.05) between the total degree of job burnout and the effectiveness of performance, The importance of this study is evident in a number of points, the most important of which is raising the level of awareness of leaders in the educational field of the importance of attention to job burnout among special education teachers and its treatment, which may positively affect the outputs of community day care centers, and the accurate identification of performance gaps among teachers with special needs in day care centers, And take the necessary actions to address them.